Developing Kruger Shalati The Train on the Bridge A Unique Modular Hotel Construction Case Study in Kruger National Park (Global Journals of Research in Engineering, 2024)
This is a case study on the development of the Kruger Shalati The Train on the Bridge a themed luxury boutique hotel in Kruger National Park KNP South Africa Two key drivers of this project were authenticity and a strong ethos for Environmental Social and Governance ESG Considering the target market the hotel serves and the local situation this case study explains why modular construction was better to build parts of the property instead of using traditional in situ construction methods It further explains how the hotel was built and the challenges that had to be addressed to complete the project Finally it examines how the use of modular construction methods and the uniqueness of the project impacted the normal hotel pre-opening activities and ongoing hotel operations This case study has been prepared after reviewing published materials about the project and extensively interviewing five senior members of the project team
Keywords: new hotel development; project management; case study; modular construction; ecotourism; experiential hospitality; kruger national park